Genetic drift of influenza A(H3N2) viruses during two consecutive seasons in 2011–2013 in Corsica, France. Issue 4 (16th September 2013) - Fantoni, Anais; Arena, Christophe; Corrias, Laura; Salez, Nicolas; de Lamballerie, Xavier Nicolas; Amoros, Jean Pierre; Blanchon, Thierry; Varesi, Laurent; Falchi, Alessandra
Abstract The 2011–2012 and 2012–2013 post‐pandemic influenza outbreaks were characterized by variability in the A(H3N2) influenza viruses, resulting in low to moderate vaccine effectiveness (VE). The aim of this study was to investigate the molecular evolution and vaccine strain match of the A(H3N2) influenza viruses, having been circulated throughout the population of the French Corsica Island in 2011–2012 and again in 2012–2013. Clinical samples from 31 patients with confirmed A(H3N2) influenza viruses were collected by general practitioners (GPs) over these two consecutive seasons. An analysis of genetic distance and antigenic drift was conducted. Based on a hemagglutinin (HA) aminoacid sequence analysis, the Corsican A(H3N2) viruses fell into the A/Victoria/208/2009 genetic clade, group 3. All influenza viruses were characterized by at least four fixed amino acid mutations which were: N145S (epitope A); Q156H and V186G (epitope B) Y219S (epitope D), with respect to the A/Perth/16/2009 (reference vaccine strain for the 2011–2012) and the A/Victoria/361/2011 (reference vaccine strain for the 2012–2013). Using the pepitope model, the percentages of the perfect match VE estimated against circulated strains declined within and between seasons, with estimations of <50%. Overall, these results seem to indicate an antigenic drift of the A(H3N2) influenza viruses which were circulated in Corsica. These findings highlight the importance of the continuous and careful surveillance of genetic changes in the HA domain during seasonal influenza epidemics, in order to provide information on newly emerging genetic variants. J. Med. Virol. 86:585–591, 2014. © 2013 Wiley Periodicals, Inc.